Investment Value In Nordic Security Analysts Recommendations? - Ojansuu, Eero (My University, 2006)
The value of equity research has been a debated subject for a long time. After the market crash in 2000 the media criticed the equity research business for misleading investors to buy stocks with no real value and at the same time collecting significant fees. This study examines theories and empirical evidence related to analysts stock recommendations. The main purpose of this thesis is to analyze equity analysts’ stock recommendations in the Nordic countries and to evaluate if the recommendations add value to investors. In this thesis I have analyzed Nordic Countries top- ranked equity research analysts recommendations on Nordic large-cap stocks between 2003−2005. The performance of equally weighted portfolios has been compared to equally weighted benchmarks of Nordic countries Stock exchanges. The portfolios, formed at preset dates in the beginning of each quarter, were based on stock recommendations from the top-ranked analysts in each industry sector of Prospera Ab’s annual analyst ranking. The stock recommendations for this study is collected from Jcf Quant database for a time period between 1st april 2003−31st june 2005. In addition I use Thomson financial database to obtain interest-rate information for the same time period. Results show evidence of stock picking ability for top ranked analysts analyzing Danish stock markets. Results were statistically significant on raw-return and risk-adjusted basis. For the other Nordic countries the results supporting stock picking ability were not statistically significant. The analyses were made using linear regression and t-test. The time span of the evaluation was limited to three years due to the limited availability of the Prospera Ab:s analyst ranking lists.
Keywords: Top Ranked Analyst; Nordic Stock Markets; Abnormal Return; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|